DOP22 Clinical, biochemical and endoscopic disease activity of Inflammatory Bowel Diseases are not associated with the severity or long-term outcomes of COVID-19 – A Danish prospective population-based cohort study. (21st January 2022) - Attauabi, M; Dahlerup, J F; Poulsen, A; Hansen, M R; Vester-Andersen, M K; Eraslan, S; Prahm, A P; Pedersen, N; Larsen, L; Jess, T; Neumann, A; Haderslev, K V; et al.
Abstract: Background: Whether the disease activity of ulcerative colitis (UC) and Crohn's disease (CD) is correlated with the severity of coronavirus disease 2019 (COVID-19) remains poorly investigated with only few selected cohort studies having addressed this in the past. Methods: We conducted a population-based study investigating the outcomes of COVID-19 among patients with UC and CD in Denmark. The Danish COVID-19 IBD Database is an extensive population-based database which prospectively monitors the disease course of laboratory-confirmed COVID-19 among patients with UC and CD. Severe COVID-19 was defined as COVID-19 necessitating intensive care unit admission, ventilator use, or death, while adverse COVID-19 was defined as requirement of COVID-19 related hospitalization. Clinical disease activity was measured by simple clinical colitis index and Harvey-Bradshaw Index in UC and CD, respectively. The biochemical activity was defined as C-reactive protein higher than 5 mg/L or fecal calprotectin higher than 250 μg/g. The endoscopic activity was defined as Mayo Endoscopic Subscore of at least 2 in UC, or Simple Endoscopic Score Crohn's Disease of at least 3 for CD. Sequelae following COVID-19 were defined as symptoms that (i) developed during or after an infection consistent with COVID-19, (ii) and were present for more than 12 weeks, (iii) and were not attributable to alternative diagnoses. Results: During the inclusion period between January 28 th, 2020, to April 1 st, 2021, the study included 319 patients with UC and 197 patients with CD who developed laboratory confirmed COVID-19. Of these, data on clinical, biochemical, and endoscopic activity were available among 265/319 (83.1%), 319/319 (100.0%), and 66/319 (20.7%) of patients with UC, respectively, and 140/197 (71.1%), 131/197 (66.5%), and 42/197 (21.3%) of patients with CD. Figures 1–2 outlines the outcomes of COVID-19 according to the degree of clinical, biochemical and endoscopic disease activity. In both UC and CD, clinical, biochemical, and endoscopic activity were not associated with adverse or severe COVID-19, nor long-term outcomes, in unadjusted nor adjusted analysis (Table 1). Conclusion: In this population-based study, we found no association between disease activity of UC or CD and severity of COVID-19. These findings have implications for the risk stratification of patients with IBD acquiring COVID-19.